The relationship between dental caries and carbohydrates intake among preschool-aged children in rural and urban areas - Fadilah, Rina Putri Noer; Nawawi, Azkya Patria; Supriatna, Andi; Sarwendah, Sri; Widyasari, Ratih (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2017)
Introduction: The prevalence of dental caries among children has increased in the past decades. Dental caries has a multifactorial aetiology, including host (saliva and teeth), microbiology (plaque), substrate (diet), and time. The role of fermentable carbohydrates intake as a risk factor in the initiation and progression of dental caries. The purpose of this study was to determine the relationship between dental caries and carbohydrates intake among preschool-aged children in rural and urban areas of the city of Cimahi, Indonesia. Methods: The method used was an analytical cross-sectional study with pathfinder survey based on the WHO basic methods of oral health surveys. The data were collected through intraoral examination, and nutritional status measurement was done by using food frequency questionnaire. Statistical analysis used was the chi-square test. Results: From the study towards 100 preschool children resulted the prevalence of dental caries in rural and urban area respectively was 96 and 92%. The average value of deft index in urban area was 8.46 (95% CI:7.00-9.91) and was 7.98 (95% CI:6.50-9.45) in rural area. The average value of sucrose intake frequency in urban area was 237.14 (95% CI:204.95-269.32), whilst in rural area was 177.54 (95% CI:155.66-199.41). Conclusion: There was a relationship between dental caries and carbohydrates intake among preschool-aged children in the rural and urban area of the city of Cimahi, Indonesia.